Sterile Neutrophilic Dermatosis (Sweet's Syndrome) Associated With Systemic Inflammatory Response Syndrome in a Maltese Dog: A Case Report - Cho, ARom; Bae, Hyeona; Shin, Sunwoo; Kim, Youngju; Jeon, Yeseul; Hyun, Jae-Eun; Cho, Kyu-Woan; Jung, Dong-In; Kim, Dae Young; Yu, DoHyeon (Frontiers in Veterinary Science, 2022)
We report a rare case of sterile neutrophilic dermatosis (Sweet’s syndrome) accompanied by systemic inflammatory response syndrome. A 5-year-old, neutered male Maltese dog presented with extensive crusts on the whole-body surface and multifocal erosions and plaques on the four limbs. The lesions had been present for two months and did not respond to antibiotics before the presentation. In addition, the dog was lethargic, anorexic, and febrile, with joint swelling. A clinicopathologic analysis revealed neutrophilic leukocytosis with left shift and increased C-reactive protein level. Furthermore, a histopathological examination showed moderate to severe inflammatory infiltrates consisting predominantly of neutrophils from the superficial to the deep dermis. There was no evidence of bacterial or fungal infections, and autoimmune diseases, such as pemphigus, systemic lupus erythematosus, and erythema multiforme, were excluded. Sweet's syndrome, a rare skin disorder, associated with systemic inflammation was diagnosed, and the cutaneous lesions and systemic inflammation disappeared after prolonged steroid administration.